MiR‐199a‐5p suppresses tumorigenesis by targeting clathrin heavy chain in hepatocellular carcinoma. (5th March 2017) - Huang, Guo‐hao; Shan, Hong; Li, Dan; Zhou, Bin; Pang, Peng‐fei
Abstract : The deregulation of microRNA (miRNA) is frequently associated with a variety of cancers, including hepatocellular carcinoma (HCC). In this study, we investigated the expression and possible role of miR‐199a‐5p in HCC. The expression of miR‐199a‐5p was measured by quantitative RT‐PCR in HCC. The effect of miR‐199a‐5p was evaluated by cell viability and colony formation assays in HCC cell lines and tumor cell growth assay in xenograft nude mice. Quantitative real time PCR results showed that miR‐199a‐5p was down‐regulated in 77.9 % (67/86) of HCC tissues compared with adjacent nontumor tissues. MiR‐199a‐5p mimic reduced cell viability and colony formation by induction of cell arrest in HCC cell lines and inhibited tumor cell growth in xenograft nude mice, but miR‐199a‐5p inhibitor increased cell viability and colony formation in HCC cell lines and tumor cell growth in xenograft nude mice. Furthermore, CLTC was defined as a potential direct target of miR‐199a‐5p by MiRanda and TargetScan predictions. The dual‐luciferase reporter gene assay results showed that CLTC was a direct target of miR‐199a‐5p. The use of miR‐199a‐5p mimic or inhibitor could decrease or increase CLTC protein levels in HCC cell lines. We conclude that the frequently down‐regulated miR‐199a‐5p can regulate CLTC and might function as a tumor suppressor in HCC. Therefore, miR‐199a‐5p may serve as a useful therapeutic agent for miRNA‐based HCC therapy.